ANALISIS SEMIOTIK DALAM KUMPULAN SAJAK KETIKA JARUM JAM LELEH DAN LELAH BERDETAK KARYA DIMAS ARIKA MIHARDJA - Jetri Ramasyahri; Sumiharti Sumiharti; Erlina Zahar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is aimed at describing the use of semiotic in Ketika Jarum Jam Leleh dan Lelah Berdetak anthology by Dimas Arika Mihardja. This research identifies the signs of meaning and interpretations towards hermeneutics approach. This research is descriptive qualitative. The population of the research is the verses in Ketika Jarum Jam Leleh dan Lelah Berdetak anthology by Dimas Arika Mihardja. In collecting the data, purposive sampling is used. The primary data is taken from verbal data in a form of words in Ketika Jarum Jam Leleh dan Lelah Berdetak anthology by Dimas Arika Mihardja, while secondary data is taken from semiotic theory and some literary books. Based on the result and discussion, it can be concluded that there are signs in Ketika Jarum Jam Leleh dan Lelah Berdetak by Dimas Arika Mihardja, they are Penikmat kehidupan anthology, they are; human being who lives in this world. Human being who are full of story, human being who wants to live happily by having the freedom whithout thinking about the consequences are ended up being despicable. Being despicable with what they have done is useless that leads them to feel regret.Key Words: semiotic, hermeneutic, anthology